2006
DOI: 10.1152/ajpheart.01055.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniaein foci of “early” calcification of the tunica media in arteriosclerotic arteries: an incidental presence?

Abstract: Only a few previous works investigated the involvement of Chlamydia pneumoniae (Chlamydophila pneumoniae) in arterial calcification. The present study investigated a possible association between C. pneumoniae and medial calcification. Carotid artery segments obtained by endarterectomy from 60 patients were examined by PCR and immunohistochemistry to identify the presence of C. pneumoniae. Arterial specimens showing double-positive (n = 17), double-negative (n = 22), and single-positive results (n = 21) were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…This first suggestion of infection was observed in the 1970s on noting the presence of monoclonal SMCs. 22 Observed presence of Chlamydia in foci of tunica media calcifications 23 suggested the hypothesis of infection of SMCs by Chlamydia as the initiating point in atherosclerosis. Another theory is the observed double-infection by both Chlamydia and CMV causing a synergistic increase in inflammatory response and perhaps speeding atherosclerosis progression.…”
Section: Infectionmentioning
confidence: 98%
“…This first suggestion of infection was observed in the 1970s on noting the presence of monoclonal SMCs. 22 Observed presence of Chlamydia in foci of tunica media calcifications 23 suggested the hypothesis of infection of SMCs by Chlamydia as the initiating point in atherosclerosis. Another theory is the observed double-infection by both Chlamydia and CMV causing a synergistic increase in inflammatory response and perhaps speeding atherosclerosis progression.…”
Section: Infectionmentioning
confidence: 98%
“…Archival tissue specimens, some characteristics of which were reported previously [15,16,44] , were used in the present study and represented carotid artery tissues obtained by endarterectomy from 39 patients whose ages ranged from 52 to 75 years (24 males and 15 females) [15] . The study was carried out in accordance with the principles outlined in the Helsinki Declaration and informed consent was obtained from each patient [15] .…”
Section: Tissue Specimensmentioning
confidence: 99%
“…Several studies have suggested that infection may play a role in the development of calcification (10, 11). Pathogens such as Chlamydia pneumoniae infect human macrophages, endothelial cells and arterial smooth muscle cells (12), and induce production of cytokines and matrix metalloproteinases, thus potentially contributing to calcification (11, 13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens such as Chlamydia pneumoniae infect human macrophages, endothelial cells and arterial smooth muscle cells (12), and induce production of cytokines and matrix metalloproteinases, thus potentially contributing to calcification (11, 13, 14). An intense inflammatory process by pathogen infection may result in debris of cellular membranes of the bacteria and host cells, creating a substrate for calcium deposition (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation